The impact of bridging therapy prior to CD19‐directed chimeric antigen receptor T‐cell therapy in patients with large B‐cell lymphoma. (9th September 2021) - Lutfi, Forat; Holtzman, Noa G.; Kansagra, Ankit J.; Mustafa Ali, Moaath; Bukhari, Ali; Yan, Jingsheng; Samanta, Santanu; Gottlieb, David; Kim, Dong W.; Matsumoto, Lisa R.; Gahres, Natalie; Ruehle, Kathleen; et al.
Summary: In the relapsed/refractory setting for treatment of large B‐cell lymphoma (LBCL), chimeric antigen receptor T‐cell (CAR‐T) therapy has emerged as an effective treatment modality. Patients often have aggressive disease that requires prompt treatment in the form of bridging therapy (BT) for disease stabilisation while CAR‐T cells are manufactured. Patients ( n  = 75) undergoing CAR‐T therapy infusion for LBCL at our institution were identified. A total of 52 (69·3%) received BT and 23 (30·7%) received no BT (NBT). BT modalities included systemic BT (SBT) in 28 patients, radiation BT (RBT) in 14, and high‐dose steroid BT (HDS) in 10. There was no difference in incidence of cytokine release syndrome or immune effector cell‐associated neurotoxicity syndrome between BT and NBT ( P  = 0·18 and P  = 0·53 respectively). Prolonged cytopenias at Day 180 were more common in BT than NBT (50% vs. 13·3%, P  = 0·04). The SBT and RBT subgroups had more cytopenias at Day 180 compared to the HDS and NBT subgroups (58·3% and 57·1% vs. 20% and 13·3% respectively, P  = 0·04). Disease response at last follow‐up, progression‐free survival and overall survival were similar between BT, NBT, and BT subgroups. In summary, BT can be safely considered in patients undergoing CAR‐T therapy. However, those undergoing BT with SBT or RBT are at higher risk of prolonged cytopenias after CAR‐T therapy. Abstract : Graphical schema of study: bridging therapy (BT), no BT (NBT), systemic BT (SBT), and high dose steroid BT (HDS) with reported 1‐year outcomes, cytokine release syndrome (CRS), immune effector cell‐associated neurotoxicity (ICANS), and day 180 cytopenias.